Enhancing Digital Technology Integration in Primary Education: The Impact of Teachers' Pedagogical and Professional Competence - Erviana, Vera Yuli; Saifuddin, Much Fuad; A’inayah, Ainun (Universitas Negeri Makassar, 2025)
The rapid development of digital technology requires teachers to improve their competence in effectively integrating technology into the learning process on an ongoing basis. Pedagogical and professional competence are essential in ensuring that teachers can adapt to technological changes and create meaningful and engaging learning experiences. However, many educators face challenges in optimally utilizing digital tools, so it is important to examine the relationship between their competence and the integration of digital technology. This study aims to analyze the impact of teachers' pedagogical and professional competencies on the integration of digital technology into tlearning. Using an ex-post facto quantitative research design, this study was conducted at SD Muhammadiyah Karangkajen Yogyakarta, involving 39 teachers selected through non-probability sampling, so the results have limitations in external validity and generalizability. The findings should be interpreted with caution. The research results show a significant correlation between pedagogical competencies and digital technology integration (r = 0.655, p < 0.05) as well as between professional competencies and digital technology integration (r = 0.747, p < 0.05), confirming the influence of both competencies. These findings highlight the importance of continuous professional development to strengthen teachers' ability to integrate digital tools into their teaching. This study suggests that developing pedagogical and professional competencies is essential to maximize the potential of digital technology education, which ultimately enhances students' learning experiences.